Effect of herbicides on distribution and interference of weeds, growth and yield of wheat (Triticum aestivum) in Kandahar, Afghanistan - SEN, SUMAN; ZIAR, Y K; DAS, T K; RAJ, RISHI (The Indian Journal of Agricultural Sciences, 2022)
Weeds are the major constraint to achieving higher wheat yield in Afghanistan. To evaluate weed interference and its impact on wheat, a field experiment was undertaken during winter season in 2014–15 at Afghanistan National Agricultural Science and Technology University (ANASTU), Kandahar. Seven weed control treatments comprising isoproturon 0.75 and 1.0 kg/ha at 35 days after sowing (DAS), sulfosulfuron 20 and 25 g/ha at 35 DAS, isoproturon + 2,4-D 0.75 + 0.5 kg/ha at 35 DAS (tank-mix), weed-free check and weedy check were laid out in a randomized complete block design with three replications. Results showed that grassy weeds constituted 62.7% of the total weeds and were mostly dominant. All herbicides/weed control treatments influenced weed interference, wheat cropgrowth and yield significantly. Sulfosulfuron 25 g/ha at 35 DAS resulted in significant reduction in weed density by 95.2% (i.e. weed control efficiency) and dry weight by 95.1% (i.e. weed control index), respectively. This treatment led to significant improvements in wheat growth (Leaf area index, dry matter accumulation) and grain (4.6 t/ha) and biological yields (10.6 t/ha), and was superior to other herbicide treatments. It increased wheat grain and biological yields by 24.3% and 17.8%, respectively, compared to weedy check. Therefore, the application of sulfosulfuron 25 g/ha at 35 DAS may be recommended for better weed control and higher wheat yield in Kandahar, Afghanistan, and in similar agro-ecologies of the tropics and sub-tropics.